The Impact Of Hybrid Infrastructure On Trust, Motivation And Knowledge Sharing In An Intentional Community: A Latvian Case Study - Guido Sechi; Jurgis Skilters; Marta Selecka; Krista Berzina; Liva Brice (European Regional Science Association (ERSA), 2013)
The role of ICT infrastructure in enhancing innovation processes through fostering knowledge and information exchange is a controversial topic in regional science. Opposing views exist, in particular, with regard to two topics: a) the persistence of a specific role of geographical proximity in knowledge exchange processes in the age of global virtual networking; b) the capability of virtual networking to recreate the social assets of a physical community (trust, solidarity?). Existing studies primarily focus on aggregated data, rely on doubtful epistemological assumptions (e.g. the equation of information with knowledge), and neglect several epistemological principles of social cognition (e.g. collective and collaborative agency of communities). It may be hypothesized that the debate would benefit from: a) analyses focused on the micro (individual) level; b) a more complex formalization of social dynamics; and c) a deeper reflection on the nature of cognitive factors at stake. The paper is aimed at investigating the effect that the co-existence of physical and virtual networking has on social assets building and knowledge sharing among members of an intentional community (in our study: the National Library of Latvia users? community). The theoretical framework draws on social and cognitive science, combining social capital theory, social learning theory, and theories of collective and collaborative action in cognitive social science. The theoretical model to be tested empirically relies on a complex taxonomy of social capital and shareable knowledge. The former takes into account both physical / virtual structural (network) assets and social resources which are embedded in such networks; the latter encompasses relevant dichotomies in applied and cognitive epistemology. Indirect positive effects of social capital on individual knowledge growth ? through the empowerment of community-oriented motivation and quality of knowledge exchange - are hypothesized. The empirical analysis is based on the collection of psychometric data at the micro (individual) level and on a methodological approach relying on advanced econometrics (structural equation modelling), able to encompass both measurement problems related to the intangible nature of variables, and an assessment of complex cause-effect dynamics. The analysis helps to compare the effect of physical and virtual networking in enhancing social resources and hence knowledge exchange and enrichment. In order to grasp such effects in a better way, the model is tested for clusters of community members stating preferences for either physical or virtual networking. The sensitivity of results is also tested against control variables accounting for socio-economic, demographic, ethno-cultural differences within the community.
Keywords: 330; social capital; social learning; knowledge sharing; structural equation modelling; micro scale analysis